Diminutives in Action: A cognitive account of diminutive verbs and their suffixes in Croatian - Katunar, Daniela (2013)
This paper deals with a semantic analysis of diminutive verbs in Croatian, focusing on diminutive verbs formed by diminutive suffixes. In order to account for the semantic properties of diminutive verbs, a cognitive linguistic framework is adopted and a radial category model of diminutive verb semantics is proposed. Phenomena specific to verbal semantics, such as pluractionality, are also discussed in relation to diminutive semantics. Contrary to Jurafsky (1996), the semantics of diminutive verbs is accounted for in terms of two conceptual metaphors MORE IS UP (LESS IS DOWN) and GOOD IS UP (BAD IS DOWN) that motivate the formation of diminutive meanings. The central position of the radial category is given to the category of verbs of diminished physical intensity, and two other categories are proposed, verbs of dispersive actions and pejorative verbs. The classification is based on an inventory of diminutive verbs built upon the data from the Croatian Derivational Verb Database.
ENG